A RESEARCH OF AESTHETIC MOBILE LEARNING INTERFACES FOR PRIMARY EDUCATION - Nor Fatin Farzana Zainuddin, Zuriana Abu Bakar, Noor Maizura Mohamad Noor (International Journal of Advanced Science and Technology, 2020)
Aesthetics is an important element that able to influence people attraction. Aesthetics is a branch of philosophy that are dealing with the nature of art, beauty, and taste. Aesthetics also assign as the study of sensory or sensory-emotional values, sometimes called judgments of sentiment and taste. Meanwhile, aesthetics refers to how attractive the mobile are to the user going through it. As a result, visual appearance is important in deciding the aesthetic of mobile application interfaces. Hence, aims of this paper is to construct a model that can satisfy the aesthetic need of the mobile learning interface by the literature review. This study focuses on the mobile learning interfaces because the aesthetic of the interfaces could draw student’s attention to the content of the learning modules and inspire students explore more on the learning materials. The objectives of this research are to design mobile learning interfaces based on the aesthetic design principles selected, which are balance, simplicity, equilibrium, unity and consistency, to develop a model for measuring aesthetic mobile learning interfaces by the several key elements design. In order, to construct an aesthetic measuring model for mobile interfaces, this study will employ the key element design. The expected findings of this research is the model of an aesthetic mobile learning interface that could be use as the standard guidelines in mobile learning interface design.